Comparison Between Arthroscopic and Histological International Cartilage Repair Society Scoring Systems in Porcine Cartilage Repair Model. (January 2022) - Puhakka, Jani; Salonius, Eve; Paatela, Teemu; Muhonen, Virpi; Meller, Anna; Vasara, Anna; Kautiainen, Hannu; Kosola, Jussi; Kiviranta, Ilkka
Objective: The arthroscopic and histological International Cartilage Repair Society (ICRS) scores are designed to evaluate cartilage repair quality. Arthroscopic ICRS score can give a maximum score of 12 and the histological score can give values between 0% and 100% for each of its 14 subscores. This study compares these methods in an animal cartilage repair model. This study hypothesizes that there is a significant correlation between these methods. Design: A chondral defect was made in the medial femoral condyle of 18 pigs. Five weeks later, 9 pigs were treated with a novel recombinant human type III collagen/polylactide scaffold and 9 were left untreated to heal spontaneously. After 4 months, the medial condyles were evaluated with a simulated arthroscopy using the ICRS scoring system followed by a histological ICRS scoring. Results: This porcine cartilage repair model produced repaired cartilage tissue ranging from good to poor repair tissue quality. The mean arthroscopic ICRS total score was 6.8 (SD = 2.2). Histological ICRS overall assessment subscore was 38.2 (SD = 31.1) and histological ICRS average points were 60.5 (SD = 19.5). Arthroscopic ICRS compared with histological ICRS average points or its overall assessment subscore showed moderate correlation (r = 0.49 and r = 0.50, respectively). The interrater reliability with the intraclass correlation coefficients for arthroscopic ICRS total scores, histological ICRS overall assessment subscore, and ICRS average points showed moderate to excellent reliability. Conclusions: Arthroscopic and histological ICRS scoring methods for repaired articular cartilage show a moderate correlation in the animal cartilage repair model.